Place-Naming of Tourism Destination in West Java: Morphological Study - Tiara Salsabila Fadhilah; Heri Heryono (Budapest International Research and Critics University, 2022)
Language has a very important role in a tourist destination. This paper discusses morphological process of place-naming of tourism destination in West Java. West Java is one of the provinces in Indonesia that has many tourism destination. Also it has many hidden gem tourism destination that are not widely known by foreigner. The names of tourism destination in West Java have different morphological processes. The method used in this research paper is using qualitative research with descriptive approach. The purpose of this paper are Identifying kinds of morphological process and identifying the most effective process used in place-naming of tourism destination in West Java. The result demonstrated that there are found four types of morphological process in place naming tourism destination in West Java, namely acronym (29%) compounding (43%) blending (14%) and borrowing (14%).